2013
DOI: 10.1021/jp312048k
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Melting Behavior of Au–Pt Core–Shell Nanoparticles from Atomistic Simulations

Abstract: Comprehensive understanding of thermodynamic properties of metallic nanoparticles is of significance for their utility in catalysis. In this article, we have employed molecular dynamics simulations with quantum Sutton−Chen many-body potentials to examine the thermal stability of Au−Pt core−shell nanoparticles with different sizes during continuous heating. Our study shows that, for fixed particle size, the melting temperature is independent of core size for a small core while it is linearly decreased with a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 49 publications
1
63
1
Order By: Relevance
“…However, coating of a shell on top of the nanowire may affect the melting temperature of the core/shell nanowire, another important parameter which needs attention. Recently Sun et al investigated the melting behavior of metallic core/shell and alloyed nanoparticles extensively [41,[43][44][45][46]. They found that the melting behavior of core/shell nanoparticles significantly differs from that of its constituent materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, coating of a shell on top of the nanowire may affect the melting temperature of the core/shell nanowire, another important parameter which needs attention. Recently Sun et al investigated the melting behavior of metallic core/shell and alloyed nanoparticles extensively [41,[43][44][45][46]. They found that the melting behavior of core/shell nanoparticles significantly differs from that of its constituent materials.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, many experimental investigations have been carried out to synthesize and characterize different kinds of core/shell structures such as ZnO/ZnS [13], ZnO/CdS, [14] GaN/GaP, ZnO/TiO2 [15,16], CdSe/CdS [17,18], PbSe/CdSe [19,20], ZnS/CdS [21][22][23][24][25], CdS/ZnS [21,26,27], Ge/Si [28]. Both the classical molecular dynamics (MD) and density functional theory (DFT) methods have been used extensively to study the electronic [29][30][31][32][33][34][35], optical [29,36] and thermal [37][38][39][40][41][42][43][44][45][46][47][48] properties of the core/shell nanostructures. In contrast, mechanical properties of the core/shell nanostructures have so far not been investigated in details.…”
Section: Introductionmentioning
confidence: 99%
“…42 In the hydrogen adsorption/desorption region (À0. 19 It can be seen in Figure 2a,b that with increased cycling a new peak grows in at 0.5 V on the cathodic scan. This peak corresponds to the reduction of oxidized Pd on a {100} facet and grows in next to the peak at 0.35 V corresponding to the reduction of oxidized Pd on a {111} facet.…”
Section: Articlementioning
confidence: 91%
“…Computational studies modeled the high-temperature melting of AuÀPt coreÀshell NPs, finding the migration of Au from core to shell to be inhomogeneous and dependent on shell thickness. 19 A recent experimental study used various calcination temperatures and gas environments to migrate Au in AuÀPt coreÀshell NPs and manipulate the ratio of Pt to Au in the alloyed shell, finding that the migration of Au from core to shell increased catalytic activity in electro-oxidations. They attributed this result to electronic and synergetic effects: the Au in the shell both altered Pt's electronic structure and manipulated the types of active sites available.…”
mentioning
confidence: 99%
“…The Q-SC potential function provided an accurate description of inter-atomic interactions of monometallic clusters and obtained reasonable predictions of the thermodynamic and structural properties [23][24][25][26][27]. In addition, the Q-SC potential was widely used in atomistic simulation studies of alloy clusters, and shown good agreement with the results of experiment and theory [28][29][30][31][32].…”
Section: Potential Functionmentioning
confidence: 64%